Impact of waist circumference on red blood cells size in obese adults - R., Babitha; Ramanathan, RGunasekaran (International Journal of Research in Medical Sciences, 2017)
Background: Obesity is a chronic disease of multifactorial origin. Major cause for obesity is imbalance between energy intake and energy expenditure. One among the important public health problem in developing countries is increase in the prevalence of obesity. Obesity can be general obesity and central obesity. The central obesity is more dangerous than general obesity, since the central obesity reflects abdominal visceral fat, which acts as an endocrine organ and release several pro inflammatory cytokines, which leads to oxidative stress which in turn causes anisocytosis (variation in the size of the RBCs). Waist circumference indirectly measures this abdominal obesity. This study is aimed at finding the impact of Waist circumference on RBC size in obese adults. Methods: This study was done in 100 subjects in the age group 25 to 50 years (50 control with normal waist circumference and 50 obese subjects with increased waist circumference) of Annapoorana Medical college hospitals. Patients with anaemia, malnutrition, and other chronic diseases who are RBCs may show anisocytosis were excluded. Waist circumference was measured. Peripheral smear was prepared and stained with leishman’s stain. Smear was focused under oil immersion objective, and the image was captured using a digital camera. Image was transferred to the computer system and RBC diameter was measured using UTHSCA image tool software. Variation in size of the RBCs between control and subjects was compared using Pearson’s product moment correlation coefficient and Paired sample t test. Results: The variation in the size of RBCs (anisocytosis) was more in subjects with increased waist circumference when compared with subjects of normal waist circumference. By using Pearsons product moment correlation coefficient, significant r value of 0.5 and 0.7 were got in male subjects and female subjects respectively. Comparing waist circumference and anisocytosis using Paired sample t test, significant p value of ˂ 0.05 was got in male and female obese subjects. Conclusions: The oxidative stress caused by the cytokines released by the adipocytes causes decreased deformability of RBCs and cause anisocytosis, which further causes complications.